INTEGRATION OF INTERCULTURAL AND SPECIALLY PROFESSIONAL COMPETENCIES FOR IMPLEMENTATION OF INTEGRATED COMPETENCY IN THE SPHERE OF FASHION DESIGN - Ryabchykova, K. (Problems of Engineer-Pedagogical Education, 2018)
The place of intercultural competence in the general structure of the professional competences of specialist in the field of fashion design is defined. The special importance of the formation of intercultural competence for the training of a global student, as a composition of communication, cultural intelligence and professional intercultural abilities is proved. The analysis of structurally logical connections in the process of forming the basic competences of the designer of clothes is carried out. The ways of forming integral competence are determined. The main structural approaches to the introduction of the intercultural competence of the designer of clothes are offered. The schemes with parallel, sequential, individually parallel, combined formation of intercultural competence are developed. The parallel scheme is characterized by additional special courses on the formation of common intercultural competencies, as well as language practices. The sequential scheme assumes the integration of the special competencies of the designer of clothing in special pre-degree intercultural courses and an intercultural diploma project. An individual scheme presupposes the formation of intercultural competence within individual professional competences. The combined scheme combines the basic algorithms.